The Role of Soft Skills Training on Employability with Self-Efficacy as an Intervening Variable: A Study on Management Students at Makassar State University - Sahabuddin, Romansyah (PT. Maju Malaqbi Makkarana, 2024)
This study aims to analyze the effect of soft skills training on employability of students of the Management Study Program, Faculty of Economics and Business, Makassar State University, with self-efficacy as an intervening variable. Employability is the ability of graduates to enter the world of work, which is not only determined by technical knowledge, but also soft skills such as communication, teamwork, and leadership. This study used the SEM-PLS approach to analyze data obtained from 116 student respondents. The results showed that soft skills training has a positive and significant effect on employability. In addition, self-efficacy also acts as a significant intervening variable, although the direct effect of self-efficacy on employability is lower than the effect of soft skills training. The final conclusion of this study shows that an effective soft skills training program can increase student employability, both directly and through increased self- efficacy.